Adult-type hypolactasia in children: A genetic perspective - Kuchay, Raja A.H.; Mahmood, Akhtar; Mahmood, Safrun (Journal of Pediatric Biochemistry, 2012)
Adult-type hypolactasia is an autosomal recessive condition resulting from the physiological decline of the lactase enzyme activity in intestinal cells which occurs in a significant proportion of the global population. Mechanisms proposed to explain the occurrence of adult-type hypolactasia include: (a) decreased production of lactase, (b) synthesis of an inactive high molecular weight lactase, (c) defective post-translational modifications, and (d) susceptibility of lactase to luminal proteases during weaning due to change in levels of sialylated and fucosylated enzymes in the small intestine. Recently, the C/T-13910 polymorphism on chromosome 2q21 in North-European populations has been found to be associated with lactase activity and its genetic typing is advocated as a first-stage screening test for adult hypolactasia. Available biochemical methods for diagnosis of adult-type hypolactasia consists of the lactose tolerance test (LTT), which measures the increase in blood glucose after an oral lactose load, and the hydrogen breath test (HBT), that is based on the determination of exhaled hydrogen produced by the bacterial flora in the colon after an oral lactose load. These methods require significant procedural time both for the patient and the processing clinical laboratory. The present review describes genetic regulation of lactase expression and various single nucleotide polymorphisms (SNPs) associated with adult-type hypolactasia and lactase persistence in different human populations.
Keywords: Adult-type hypolactasia; genetic regulation; genetic testing